A review of aflatoxin M1 in liquid milk - Maryam Jalili; M Scotter (Iranian Journal of Health, Safety and Environment, 2015)
Mycotoxins continue to pose a health concern via human exposure to contaminated food. Aflatoxin M1 (AFM1), the hydroxylated metabolite of aflatoxin B1 (AFB1), may be found in the milk of dairy cattle and other mammals. In humans, AFM1 is excreted through the feces, urine, and in the case of lactating mothers, also in breast milk after consumption of aflatoxin contaminated food. Concentration of AFM1 in milk is a function of several factors, namely: animal type, milking day, milk yield, season, feeding regime, geographic, and climatic conditions. A linear relationship has been established between the amount of AFM1 in milk and the amount of AFB1 in feed consumed by animals, emphasized at first on the reduction or removal of AFB1 from feedstuffs and then elimination of AFM1 from milk. This review aims to bring up to date the current global status of AFM1 contamination of liquid milk destined for human consumption and the effects of processing and reduction methods on the elimination of aflatoxins from liquid milk.